Evaluation of Flow Behavior Around an Airfoil Body - Sharma, Aman (My University, 2012)
A wooden NACA 2415 airfoil is fabricated with four static pressure taps for measurement of surface pressure. The main objective of this investigation is to analyze the flow behavior around the airfoil body and to calculate the performance coefficients at Reynolds Number 1.04×105 and angle of attack from -50 to 180. The section-lift and drag coefficient for an asymmetric airfoil are obtained by analyzing the measured pressure distribution at pressure taps on the airfoil surface. The airfoil spans the test section. A U-tube manometer is used to monitor the surface pressure and provide a visual display of the dynamic changes associated with varying angle of attack. The experimental data for NACA 2415 from wind tunnel is validated with simulations computed in the software FLUENT. The airfoil is cambered and measures 100 mm. The lab data and simulations are performed at various angles of attack and lift and drag coefficients are computed. By plotting the curve L/D yields the most efficient airfoil angle of attack, found to be 170. Viscous model Spalart-Allmaras, k-ε and k-ω are used in FLUENT. The simulations in FLUENT yielded the best correlation to the experimental data with the viscosity model k-ω and had the overall best performance in determining the lift and drag coefficients. Lift increases as the angle of attack increases between -5 and +17 degrees and at +17 degrees maximum lift is generated. If the angle of attack is increased any further drag becomes the dominant factor and the wing enters the stall mode.
Keywords: Airfoil; Simulation; NACA 2415